Edukasi Untuk Meningkatkan Tingkat Pengetahuan Ibu Tentang ISPA Di RW 05 Kertamaya Bogor Selatan - Lannasari, Lannasari; Solehudin, Solehudin; Herliana, Irma; Koto, Yeni; Lestari, Nur Eni (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Public education about ARI is important to reduce the spread of the disease and its impact. Good knowledge about ARI can help the community prevent the spread of this disease and reduce its impact, especially among vulnerable groups such as children. Counseling also encourages better preventive measures and quick and appropriate treatment. Similar educational programs need to be continuously held to improve overall public health. The purpose of this activity is to increase the level of public knowledge about ARI. Community service activities are carried out by professional nurse lecturers who teach community and family nursing courses. Community service together with professional nurse students who are practicing community and family nursing. Community service activities are health counseling. The counseling and simulation were carried out on Saturday, June 13, 2024 at 09.00 - 12.00 WIB in the Madrasah Marga Jaya room, RT 02 RW 05, Kertamaya Village, South Bogor District, Bogor City, West Java. After being given counseling to the community, the level of knowledge of mothers about ARI increased after being given counseling about ARI. This educational activity successfully achieved its goal of increasing the level of knowledge of mothers about ISPA and providing a significant positive impact on the health of children and the community.